Accountabilities in the NHS: Coercion, Finance and Responsibility. Issue 1 (1st March 2023) - Pushkar, Piyush
Abstract: This article is based on ethnographic fieldwork carried out with managers, politicians and political activists in the English public healthcare system. Rather than a dominance of financial accountability, I found a mish-mash of accountabilities, in which the duty to 'balance the books' was a key driver but one that relied on other forms of coercion. Campaigners mobilised the concept of political accountability against cuts and privatisation. While bureaucrats were often sympathetic to activists' point of view, they felt constrained by 'the reality' of limited funds. Their conceptualisations of what was possible were enclosed . Debate regarding those limits was foreclosed . I sketch these limits on bureaucrats' ethical imagination, theorising them as ideological closure . But at times, managers did imagine alternative possibilities. Mostly, they kept quiet regarding alternatives due to a fear of losing their jobs. Thus, corporate accountability – to one's employer – enforced service retrenchment in the name of financial accountability.